Life cycle assessemnt (LCA) study of a milk powder product in aluminium foil packaging - Venessa Allia Aiman; Mochammad Chaerul; Benno Rahardyan (Indonesian Life Cycle Assessment Network (ILCAN), 2018)
Dairy processing industry is one of the industries that give positive contribution to the economic growth, however it also contributes in many impacts on the environment, as well as milk powder product manufactured by PT X. The main objective of this study was to determine the most significant environmental impact caused by production and transportation of milk powder in bag 250 gram (Product X) using Life Cycle Assessment (LCA) methodology. The boundary of the LCA study is “cradle to gate”, including: materials production, materials transportation from supplier to the PT X factory, manufacture of milk powder in PT X, and distribution of the products from factory to distributor. Four impact categories will be calculated on this study: global warming potential (GWP), eutrophication potential (EP), acidification potential (AP), and photochemical oxidant creation potential (POCP). The impact assessment was calculated by software SimaPro v.8.3.2 faculty license, and the calculation result validated manually by Microsoft Excel. The result of environmental impact calculation showed the GWP, EP, AP, and POCP of 1 kg milk powder is 1.3245 kg CO2 eq/kg, 0.0033 kg PO43- eq/kg, 0.0066 kg SO2 eq/kg and 0.0020 kg C2H4 eq/kg. The material production subsystem has the highest environmental impact on GWP, POCP, AP and EP categories. In particular, production activity in PT X also contributes to GWP. An environmental impact reduction strategy can focus on reducing GWP with electricity usage efficiency and developing a material supplier selection plan with environmental impacts of material production as one of criteria.